Evaluasi Penjaminan Mutu Internal di Perguruan Tinggi - Supriyanto, Supriyanto; Rosyanafi, Rofik Jalal; Ningrum, Mallevi Agustin; Indrawati, Delia (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2024)
Evaluation of Internal Quality Assurance at the Faculty of Education, Surabaya State University and carried out by a research team from the Faculty of Education, UNESA. The aim of the research is to evaluate the internal quality assurance process at the faculty. Carried out for 1 year and funded by LPPM UNESA. Evaluation focuses on learning monev and curriculum audit. The results show that the implementation of learning monev and curriculum audits is in accordance with the schedule set by the Chancellor. This evaluation provides information that can be used for policy making regarding internal quality assurance within the scope of the study program. The research method used is the CIPP (Context, Input, Process and Product) evaluation model using a questionnaire as a research instrument. Even though there are several obstacles in its implementation, the general evaluation of the implementation of internal quality assurance at FIP ??Unesa shows good results.